Protecting the Eye Lens from Oxidative Stress through Oxygen Regulation - Witold Karol Subczynski; Marta Pasenkiewicz-Gierula; Justyna Widomska (MDPI AG, 2023)
Molecular oxygen is a primary oxidant that is involved in the formation of active oxygen species and in the oxidation of lipids and proteins. Thus, controlling oxygen partial pressure (concentration) in the human organism, tissues, and organs can be the first step in protecting them against oxidative stress. However, it is not an easy task because oxygen is necessary for ATP synthesis by mitochondria and in many biochemical reactions taking place in all cells in the human body. Moreover, the blood circulatory system delivers oxygen to all parts of the body. The eye lens seems to be the only organ that is protected from the oxidative stress through the regulation of oxygen partial pressure. The basic mechanism that developed during evolution to protect the eye lens against oxidative damage is based on the maintenance of a very low concentration of oxygen within the lens. This antioxidant mechanism is supported by the resistance of both the lipid components of the lens membrane and cytosolic proteins to oxidation. Any disturbance, continuous or acute, in the working of this mechanism increases the oxygen concentration, in effect causing cataract development. Here, we describe the biophysical basis of the mechanism and its correlation with lens transparency.